The burden of cervical cancer survivorship: Understanding morbidity and survivorship needs through hospital admissions - Rayne Peerenboom; Sarah Ackroyd; Nita Lee (Gynecologic Oncology Reports, 2024)
Objective: To describe disease- and treatment-related survivorship burden amongst survivors of cervical cancer and identify risk factors for hospital admissions after initial treatment. Methods: Retrospective chart review including patients treated for cervical cancer from 2014 to 2020 at a single urban academic institution. Clinical, demographic, and hospital admission characteristics were summarized. Associations between patient characteristics and likelihood of admission were examined using univariate and multivariate regression. Results: Of 366 patients undergoing surveillance following completion of primary treatment, 156 (43 %) were hospitalized for cancer or treatment-related sequela in the median follow-up of 3.6 years (IQR 1.4–6.4), with a median of 2 admissions (IQR 1–4.5) per patient and 570 unique admissions. While 65 (35 %) of admitted patients had multiple reasons for admission, the most common reasons for admission were: gastrointestinal complications (43 %), infection (38 %), genitourinary complications (33 %), and pain control (23 %). A substantial proportion of admitted patients underwent interventions including surgical procedures (57 %), transfusion of blood products (40 %), and interventional radiology procedures (28 %) and utilized supportive care services including case management (53 %), physical therapy (40 %), and occupational therapy (36 %). On multivariate analysis, odds of admission were higher among Black patients (aOR 2.4, p <.01), uninsured patients (aOR 2.7, p <.05), those with lower performance status (aOR 1.4, p <.05), and those with recurrence (aOR 5.5, p <.001). Conclusion: Survivors of cervical cancer represent a high-risk population frequently hospitalized after initial treatment. Black patients, uninsured patients, those with recurrence, and those with lower performance status faced higher odds of admission. Comprehensive, team-based care is necessary to address complex survivorship needs.